The Evolution of Natural Law from Thomas Aquinas to Modern Rationalist Thought - Rahmatina, Rahmatina; Mahendra, Alimudin; Savitri, Dara Aulia; Nasrichofifah, Fany; Nabilah, Faza; Herlina, Riza (Green Publisher Indonesia, 2025)
Natural Law represents one of the oldest schools of thought in legal philosophy, placing the foundation of law on moral and rational values inherent in human nature. Natural law emphasizes substantive justice that is universal and eternal. This study traces the development and transformation of Natural Law theory from the theological framework of Thomas Aquinas to the rationalist thought of the modern era, with the aim of understanding the relevance of Natural Law principles in contemporary legal contexts and the epistemological shift from faith to reason. Using a qualitative approach through library research and data analysis, this study compares Aquinas’s concept of Natural Law—which views law as the participation of human reason in God’s eternal law (lex aeterna)—with the views of rationalist thinkers such as Grotius, Locke, Rousseau, and Kant, who place reason as the source of legal legitimacy and natural rights independent of divine authority. The findings show that this shift marks the secularization of Natural Law, which then forms the foundation for human rights, social contract theory, the rule of law, and legal-rational legitimacy. This study concludes that the dialectic between theological and rationalist paradigms continues to influence modern legal philosophy, making universal morality, rationality, and human dignity core pillars of contemporary legal systems